Helsingin yö - Jaana Lähteenmaa; Laura Mäkelä; Mäkelä, Laura; Cantell, Timo; Lähteenmaa, Jaana; Gräsbeck, Magnus; Mäkelä, Jaana; Helsingin kaupunki. Tietokeskus (Helsingin kaupungin tietokeskus, 1995)
Sammandrag (s. 325-336): Mot natten i Helsingfors.
Keywords: kaupunkikulttuuri; paikalliskulttuuri; kulttuurielämä; osakulttuurit; äänimaisema; Taiteiden yö; elokuvataide; aiheet; kaupungit; myymälät; aukiolo; ravintolat; seksiala; taksit; homoseksuaalisuus; kahvilat; vuorokaudenajat; elämäntapa; yö; kulttuuri; kaupunkisosiologia; kulttuurisosiologia; kaupunkitutkimus; homoseksuaalit; yötyö; seksuaalivähemmistöt; vapaa-aika; pelko; yöelämä; taide; taide-elämä; nuorisokulttuuri; kultur; urban sociologi; kultursociologi; stadsforskning; homosexuella; nattarbete; sexuella minoriteter; fritid; rädsla; stadskultur; lokalkultur; kulturliv; delkulturer; ljudlandskap; Konstens natt; filmkonst; ämnen (områden); städer; affärer; öppethållning; restauranger; sexbranschen; taxibilar; homosexualitet; kaféer; dygnets timmar; livsstil; natt; nattliv; konst; konstliv; ungdomskultur; Helsinki; Helsingfors; yöelämä : helsinki; kulttuurielämä i; myymälät i; ungdomsgäng